1989
DOI: 10.1038/ki.1989.289
|View full text |Cite
|
Sign up to set email alerts
|

Long-term enalapril and verapamil in rats with reduced renal mass

Abstract: The effect of long-term treatment with either enalapril or high dose verapamil on survival, proteinuria, blood pressure and renal morphology was studied in female Wistar rats with markedly reduced renal mass. Four weeks were allowed for remnant kidney hypertrophy before determining the response to renal ablation of individual animals regarding proteinuria and hypertension. At this time, five groups of 18 rats were formed with equal levels of proteinuria and hypertension. Groups E1 and E2 were treated with enal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
3
2

Year Published

1991
1991
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(52 citation statements)
references
References 24 publications
4
43
3
2
Order By: Relevance
“…The effect of calcium channel blockers on the progression of renal failure is controversial. In contrast with earlier studies, we recently reported that moderately large doses of verapamil significantly accelerated chronic renal failure in the rat remnant kidney model [1]. Studies reporting beneficial effects of verapamil were characterised by a much lower dose of verapamil and by the start of treatment immediately after renal ablation, which potentially interfered with the initial phase of remnant kidney hypertrophy.…”
contrasting
confidence: 40%
See 2 more Smart Citations
“…The effect of calcium channel blockers on the progression of renal failure is controversial. In contrast with earlier studies, we recently reported that moderately large doses of verapamil significantly accelerated chronic renal failure in the rat remnant kidney model [1]. Studies reporting beneficial effects of verapamil were characterised by a much lower dose of verapamil and by the start of treatment immediately after renal ablation, which potentially interfered with the initial phase of remnant kidney hypertrophy.…”
contrasting
confidence: 40%
“…However, in the most extensively studied model of chronic renal failure, the remnantkidney rat, the response to different antihypertensive regimens is not uniform. Control of hypertension by ACE inhibitors has proven to be superior to triple-drug therapy with hydralazine, reserpine, and hydrochlorothiazide regarding prevention or delay in progressive glomerulosclerosis [12], and the highly protective effect of ACE inhibitors was invariably associated with greatly reduced proteinuria [1,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological analysis of tuburointerstitial lesions 94 days after induction of the nephrotic syndrome in vehicle and benidipine (1 or 3 mg/kg, p.o. )-treated rats DISCUSSION Ca-channel blockers, including benidipine, have ameliorating effects on renal function in various animal models of renal failure (2)(3)(4)17). Therefore, Ca-chan nel blockers can be expected to be drugs for protecting against the renal injury.…”
Section: Methodsmentioning
confidence: 99%
“…In various nephrosis models, hypertension, elevation of glomerular capillary pressure and renal hypertrophy are suggested as important risk factors which accelerate the development of renal disease (1)(2)(3)(4). Some authors reported that antihypertensive agents such as Ca-channel blockers and angiotensin converting-enzyme (ACE) inhibitors normalized the glomerular capillary hydraulic pressure and attenuated the progression of renal disease in a variety of ex perimental renal diseases (2)(3)(4). Thus, some antihyper tensive drugs are now clinically used for renal diseases (5)(6)(7).…”
mentioning
confidence: 99%